Generation of human iPSC line from a patient with laterality defects and associated congenital heart anomalies carrying a DAND5 missense alteration - Cristo, Fernando (2017)
A human iPSC line was generated from exfoliated renal epithelial (ERE) cells of a patient affected with Congenital Heart Disease (CHD) and Laterality Defects carrying tshe variant p.R152H in the DAND5 gene. The transgene-free iPSCs were generated with the human OSKM transcription factor using the Sendai-virus reprogramming system. The established iPSC line had the specific heterozygous alteration, a stable karyotype, expressed pluripotency markers and generated embryoid bodies that can differentiate towards the three germ layers in vitro. This iPSC line offers a useful resource to study the molecular mechanisms of cardiomyocyte proliferation, as well as for drug testing.